ANALISIS PERAN PEMERINTAH DAN MASYARAKAT DALAM MENINGKATKAN KESEHATAN DAN KESELAMATAN KERJA DI WILAYAH PESISIR - Amanda Aulia; Syavira Desputri, Sophie Zafira Tanjung, Abdurrozzaq Hasibuan (CV. Adiba Aisha Amira, 2024)
Coastal areas are potential areas of the Indonesian archipelago. Indonesia has a coastline of 81,000 km and 17,508 islands. The 4,444 fisheries in Indonesia are very large, with the potential for sustainable fishing of around 6.17 million tons per year, but only 38% of the fish in the archipelago's waters and 20% of the fish in the Exclusive Economic Zone (EEZ) waters are utilized (duffling). Occupational safety and health (K3) are the rights of workers in the formal or informal economic sector, company size and type of work. This research uses a literature analysis method which involves searching, selecting and synthesizing various articles, journals and studies related to the role of government and society in K3 in coastal areas. Data is analyzed qualitatively to identify patterns, trends and key findings related to the topic. The aim of this research is to explore and analyze the role of government and society in the context of improving K3 in coastal areas. The government's role in supporting occupational safety and health (K3) in coastal areas includes several aspects, namely technical guidance and support, monitoring the fishing and processing process, the government as a regulator, and increasing public knowledge. As well as several community roles in supporting occupational safety and health (K3) in coastal areas, namely by enthusiastically participating in socialization, applying K3 knowledge in daily life, and showing independence in implementing K3.